STATE AND NON-STATE SECTOR COOPERATION IN CULTURAL MANAGEMENT - Ravshanova Barno Ismatullayevna (International Journal of Literature and Language Studies, 2026)
This article analyzes the conceptual foundations, international experience, and current state in Uzbekistan of cooperation between the public and non-governmental sectors (business, non-governmental non-profit organizations, public foundations) in the modern management of the culture and art sector. It highlights the limitations of relying solely on the state budget to ensure cultural development, as well as the advantages of Public-Private Partnership (PPP) models. The article puts forward scientific and practical proposals and recommendations for improving the investment climate in the cultural sector, developing the creative economy, and enhancing the social partnership system in preserving the national cultural heritage.